(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The panorama of investment opportunities offered by Exchange Traded Funds (ETF’s) to investors and its momentous growth since their inception in the country has created a need to evaluate the existing literature on Indian ETF’s. Hence, the study aims to systematically review 74 research articles published in peer-reviewed journals and conferences related to Indian ETF’s. The research articles chosen for the study are scrutinized based on various attributes to highlight current trends in the literature and identify future research directions. Detailed content analysis has revealed that most of the research articles are empirical in nature that have predominantly used secondary data and the leading research theme identified is the performance evaluation of Indian ETF’s relative to other protruding areas.